The Impact of the COVID-19 Pandemic on Emergency Surgical Operations in State Hospitals in Turkey: A Retrospective and Descriptive Study - Attila Beştemir; Hakan Aydın; Alpay Tuncar (Eurasian Journal of Emergency Medicine, 2023)

(untitled)
Aim:Emergency surgery can be defined as surgical interventions and operations necessary to deal with an acute threat to life, organ, limb, or tissue. Our study examined the impact of the Coronavirus disease-2019 (COVID-19) pandemic on emergency surgical operations (ESOs) performed in state hospitals in Turkey.Materials and Methods:In this national, retrospective, and descriptive study, ESOs performed in 2nd and 3rd-level state hospitals in Turkey in 2021 were recorded for the study. ESOs performed in 2019 were taken as the control group, and the changes between the two groups were examined.Results:A total of 1,822,075 ESOs were included in the analysis. There was a 7.6% decrease in ESOs in 2021 compared to 2019. In both 2019 and 2021, cesarean section, surgical treatment of upper/lower extremity fractures and dislocations, and cholecystectomy were the most frequently performed ESOs. An increase in the number of ESOs in 2021 compared to 2019 was observed only in the urology department (7.1%) and orthopedics and traumatology department (2.7%). The surgical departments with the greatest decreases were neurosurgery (-28.1%), Otolaryngology-Head and Neck Surgery (-27.7%), and thoracic surgery (-20.9%)Conclusion:During the COVID-19 pandemic, the number of ESOs performed in the 2nd and 3rd-level state hospitals in Turkey decreased compared with the previous year.